2001
DOI: 10.1038/sj.onc.1204213
|View full text |Cite
|
Sign up to set email alerts
|

Transformation capacities of the papillary renal cell carcinoma-associated PRCCTFE3 and TFE3PRCC fusion genes

Abstract: A recurrent chromosomal abnormality associated with a subset of papillary renal cell carcinomas is t(X;1)(p11;q21). This translocation leads to the formation of two fusion genes, TFE3PRCC and the reciprocal product PRCCTFE3. Both fusion genes are expressed in t(X;1)-positive renal cell carcinomas and contain major parts of the coding regions of the parental transcription factor PRCC and TFE3 genes, respectively. To ®nd out whether these fusion genes possess transforming capacity, we transfected NIH3T3 and rat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…In contrast to the as yet undefined role of the 2 ASPL-TFE3 fusion proteins in ASPS, the PRCC-TFE3 fusion proteins associated with papillary renal carcinoma have been shown to have transforming potential. 10 Recently Mathur and Samuels 11 showed that the PSF-TFE3 fusion could transform 3T3 cells and act as a functional transcription factor. Indeed fusions of TFE3 with yet additional genes are associated with renal cancers [12][13][14] and supports the notion that aberrant transcription mediated by the TFE3 constituent of the fusion protein plays a key role in the pathogenesis of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the as yet undefined role of the 2 ASPL-TFE3 fusion proteins in ASPS, the PRCC-TFE3 fusion proteins associated with papillary renal carcinoma have been shown to have transforming potential. 10 Recently Mathur and Samuels 11 showed that the PSF-TFE3 fusion could transform 3T3 cells and act as a functional transcription factor. Indeed fusions of TFE3 with yet additional genes are associated with renal cancers [12][13][14] and supports the notion that aberrant transcription mediated by the TFE3 constituent of the fusion protein plays a key role in the pathogenesis of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the Nterminal 156 amino acids of PRCC, when fused to TFE3, significantly elevate the transactivating capacity of this fusion protein as compared with wild-type TFE3 (18). Moreover, transfection studies with conditionally immortalized mouse renal proximal epithelial cells, from which chromophilic tumors are thought to arise, showed that PRCCTFE3 could bypass temperature-induced growth arrest and differentiation (19). On the basis of the limited functional information available, we chose to further characterize PRCC via the identification of interacting proteins through yeast two-hybrid screening.…”
mentioning
confidence: 96%
“…Here we have studied its effects at molecular level using UOK146, a human Renal Cell Carcinoma cell line as model system for better understanding of anti-tumor action of A. racemosus leaf extract in vitro. UOK146 cell line has chromosomal translocation leading to synthesis of PRCCTFE3 fusion protein which is responsible for oncogenesis (Sidhar et al, 1996;Weterman et al, 2001). So the level of fusion protein/transcript was measured for evaluating the anti-cancerous effect of A. racemosus leaf extract.…”
Section: Introductionmentioning
confidence: 99%